Potential pregnancy days lost: an innovative measure of gestational age - Carmen Simone G Diniz; Jessica Reis-Queiroz; Carlos A. Kawai; Marcel Reis Queiroz; Eliana de Aquino Bonilha; Denise Yoshie Niy; Sonia Lansk; Brena Sena (Universidade de São Paulo, 2020)
ABSTRACT In Brazil, the excess of interventions that anticipate childbirth, such as cesarean sections and labor inductions, has resulted in the shortening of pregnancy, with negative consequences on maternal-infant outcomes. This commentary presents a novel way to measure gestational age: the continuous variable "Potential pregnancy days lost." Using data from the Live Birth Information System (SINASC), we counted the missing days between the period until childbirth and the average duration of pregnancy (280 days), or the lost weeks. This measure can be used as an outcome variable (socioeconomic-demographic characteristics of the mother, type of childbirth, financing, etc.) or exposure variable (for neonatal, infant, and maternal outcomes). The indicator can be used in municipal and national cohorts and intervention studies to analyze hospitals and regions. We discuss the limits and scope of gestational age measures and, given their inaccuracies, the importance of studying their trends.